2016
DOI: 10.4236/crcm.2016.56039
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Rheumatic Pulmonary Valve Disease—Case Reports

Abstract: Rheumatic heart disease (RHD) is the most common cause of acquired heart disease in children and young adults worldwide and particularly developing countries continuing to experience a high incidence of this disease. The unexpected increase in the incidence of the disease in certain areas may explain the clinical and epidemiological characteristics of this disease. The key manifestation of RHD is the cardiac valvular abnormalities characterized principally by deforming the layered and avascular leaflet archite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Damage to the pulmonary valve caused by rheumatic fever is extremely rare, but this study showed involvement of the pulmonary valve in RHD, as pulmonary regurgitation, particularly in children more than in the young adult population; albeit being the least involved and always in combination with other valves. One study in India reported two cases of isolated pulmonary lesion of rheumatic origin in children under 15 years old (31) and one reported pulmonary valve involvement combined with other valves in 2.55% of cases in Nepal (19).…”
Section: Types Of Valvular Lesionsmentioning
confidence: 99%
“…Damage to the pulmonary valve caused by rheumatic fever is extremely rare, but this study showed involvement of the pulmonary valve in RHD, as pulmonary regurgitation, particularly in children more than in the young adult population; albeit being the least involved and always in combination with other valves. One study in India reported two cases of isolated pulmonary lesion of rheumatic origin in children under 15 years old (31) and one reported pulmonary valve involvement combined with other valves in 2.55% of cases in Nepal (19).…”
Section: Types Of Valvular Lesionsmentioning
confidence: 99%
“…Pulmonary valve stenosis caused by rheumatic disease is quite rare and, when it occurs, it is almost always accompanied by rheumatic lesions of other heart valves. A few cases of rheumatic pulmonary valve disease were reported in 2016 in children under the age of 15 in the tropical zone of India and most of them presented with various degrees of pulmonary stenosis without the involvement of other cardiac valves (3). Severe isolated primary rheumatic tricuspid and pulmonary insufficiency with normal left-side heart valves is extremely rare and almost always accompanied by endocarditis, carcinoid syndrome and trauma (4,5).…”
Section: Introductionmentioning
confidence: 99%